BAMBUSA BALCOOA ROXB. : A NOVEL REMEDY FOR PEPTIC ULCER - Upreti, Anil; Byanju, Bibek; Pokhrel, Binod; Kuinkel, Samir; Bhusal, Arjun; Thapa, Nita; Suwal, Meena M.; Lamichhane, Janardan; Gauchan, Dhurva P. (Kathmandu University Journal of Science, Engineering and Technology, 2016)
Analysis of bamboo species namely B. balcooa obtained from the Sindhuli district of Nepal was carried out. Phytochemical analysis between the stem and leaves extract in six solvent was carried out. Highest yield of 34.55% of B. balcooa leaves in methanol as extracting solvent was obtained. Phytochemical analysis exhibited the presence of sterols, coumarins, reducing sugar, cardiac glycoside, flavonoids, and other polyphenolic compounds. Pharmacological analysis of methanol B. balcooa leaves extract revealed anti- ulcer activity of (14.66% protective ratio). The data are expressed as Mean ±SD which were further subject statistical analysis using Origin Pro and SPSS. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 88-95